Can the Mortensen‐Pissarides Model with Productivity Changes Explain U.S. Wage Inequality? - Wong, Linda Y. (Journal of Labor Economics, 2003)
This article examines whether the Mortensen‐Pissarides matching model with productivity changes can explain the time pattern of wage inequality. The main finding is that the model produces counterfactual results. The main source of failure seems to be the exogenous matching function and/or the exogenous surplus share, neither of which allows firms to use wage policies to direct workers’ searches.